2018
DOI: 10.1007/s00431-018-3191-1
|View full text |Cite
|
Sign up to set email alerts
|

Using a high-flow nasal cannula provides superior results to OxyMask delivery in moderate to severe bronchiolitis: a randomized controlled study

Abstract: HFNC use decreased the treatment failure rate and the duration of both oxygen therapy and ICU treatment compared to the diffuser mask, which implies that an HFNC should be the first choice for treating patients admitted to the ICU with severe bronchiolitis. What is known: • A high-flow nasal cannula (HFNC) does not significantly reduce the time on oxygen compared to standard therapy in children with moderate to severe bronchiolitis. Observational studies show that, since the introduction of HFNC, fewer childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 22 publications
0
42
0
4
Order By: Relevance
“…A growing body of evidences indicate that in spontaneously breathing subjects at risk of or with established lung injury, NHF is an effective strategy compared to conventional low flow oxygen [ 19 ]. The first clinical context for application of NHF was in neonates and infants where it is largely used to decrease risk of re-intubation [ 20 ] and manage acute respiratory pathologies such as bronchiolitis [ 21 , 22 ], asthma and croup [ 23 ]. In adults, NHF became extremely popular after publication of the FLORALI study [ 18 ] which demonstrated lower intubation and mortality rates in AHRF patients treated with NHF in comparison with noninvasive ventilation and conventional oxygen therapy.…”
Section: Resultsmentioning
confidence: 99%
“…A growing body of evidences indicate that in spontaneously breathing subjects at risk of or with established lung injury, NHF is an effective strategy compared to conventional low flow oxygen [ 19 ]. The first clinical context for application of NHF was in neonates and infants where it is largely used to decrease risk of re-intubation [ 20 ] and manage acute respiratory pathologies such as bronchiolitis [ 21 , 22 ], asthma and croup [ 23 ]. In adults, NHF became extremely popular after publication of the FLORALI study [ 18 ] which demonstrated lower intubation and mortality rates in AHRF patients treated with NHF in comparison with noninvasive ventilation and conventional oxygen therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Of the complementary approaches, only the Automated Full Search located all four of the trials that were found using the reference standard full update search. These were located between 6 and 12 months earlier than via the reference standard, in months 1 [24], 5 [25], and 7 [22,23]. The Automated Full Search also had the best precision among the complementary approaches (0.49%) and therefore the smallest number needed to read (NNR; 204 records).…”
Section: Resultsmentioning
confidence: 99%
“…The HFNC has been demonstrated to have had a bene cial effect on treatment failure, but many authors criticize this effect for the absence of effects on other related outcomes. For example, only one clinical trial included in the previously mentioned systematic review (39) found an effect on LOS and the duration of oxygen therapy, and in none of the trials included was there an effect on the probability of PICU transfer. It is clear that there was no impact in this trial on the risk of admission to PICU because all patients with CN failure went onto HFNC, while those with HFNC failure went directly to PICU in these studies.…”
Section: Discussionmentioning
confidence: 99%